الضوابط الشرعية للعقود المالية المركبة : المشاركة المتناقصة أنموذجا - محمد سيلا، محمد الأمين (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
This research aims at examining an applied and a deep-rooted juristic study on composite monetary transactions based on diminishing Musharakah. Its goals are to identify with intricacy and in detail the true nature of the types of Hybrid Financial contracts, and to find out its jurisdiction in Islamic law, to clarify the sayings of Muslim scholars on the essence of money and to come up with the preponderant or preferable sayings of jurists on them. The research strives to identify the nature and causes of the composites on transactions and to explain the difference between the composite and non-composite transactions. It illustrates the sayings of jurists on the regulations of financial transactions, inquiries into the reality of decreased partnership, and into the divisions on financing by partnership. The research also makes a thorough clarification of the position of Islamic law on the forms of decreased partnership, on the operational levels that occur to those forms, on the conditions and regulations of dealing with decreased partnership and on the practical forms for composite monetary transactions on diminished partnership. The methodology that is employed in this research is inductive and analytic. It also compares the opinions of the jurists in a comprehensive discussion. The result of this research, among others, is that decreased partnership is established and affirmed by Islamic law. The research recommends that scholars should re-examine the jurisdiction on diminishing Musharakah for it does not resemble part of the credit operation, the sale by payment and the two sales in one.